2006
DOI: 10.13057/biodiv/d070223
|View full text |Cite
|
Sign up to set email alerts
|

Study of burahol (Stelechocarpus burahol (Blume) Hook & Thomson) as an antioxidative compounds containing fruit

Abstract: Burahol (Stelechocarpus burahol (Blume) Hook & Thomson) is one of fruit tree that originally was founded in Indonesia. Traditionally burahol is used as natural deodorance, but due to low economic value, the cultivation program of this plant species is almost abandoned. Regarding to this situation, currently this plant species could be categorized as one of endangered species. At present, economic value of this fruit is almost neglected and this is the main reason why not many people interested to cultivate thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…The historical and functional trees of Stelechocarpus burahol or kepel apple, favorite fruits of Javanese princesses in Yogyakarta Sultanate, are rarely planted on the areas of Yogyakarta City and most local residents have not tasted the fruits that produce high anti-oxidative compounds that are very useful when consumed (Ramadhan et al, 2016). Unfortunately, kepel apple trees are nearly extinct (Tisnadjaja et al, 2006) and therefore, conservation efforts are needed. This is inline with the results of the previous studies by Irwan and Sarwadi (2017) the local residents of Yogyakarta City have not paid attention on the historical trees, which symbolize the territory.…”
Section: Resultsmentioning
confidence: 99%
“…The historical and functional trees of Stelechocarpus burahol or kepel apple, favorite fruits of Javanese princesses in Yogyakarta Sultanate, are rarely planted on the areas of Yogyakarta City and most local residents have not tasted the fruits that produce high anti-oxidative compounds that are very useful when consumed (Ramadhan et al, 2016). Unfortunately, kepel apple trees are nearly extinct (Tisnadjaja et al, 2006) and therefore, conservation efforts are needed. This is inline with the results of the previous studies by Irwan and Sarwadi (2017) the local residents of Yogyakarta City have not paid attention on the historical trees, which symbolize the territory.…”
Section: Resultsmentioning
confidence: 99%
“…Another popular species used for an oral deodorant and body-odor remover is kepel fuit or Stelechocarpus burahol (Darusman et al 2012). According to Tisnadjaja (2006), kepel or burahol fruit has traditionally been used as a perfume material, especially in palaces; consuming the fruit can convey its scent to sweat, breath and even urine.The genus Monodora produces fragrant flowers. In addition, the flesh of its fruit yields essential oils used for perfumes, soaps, and detergents (Eze-Steven et al 2013),…”
Section: Cosmetics and Perfumesmentioning
confidence: 99%
“…These species are widely grown both individually and in plantation. However, other species, such as Annona glabra, A. montana, Alphonsea teysmanii, A. javanica, and Stelechocarpus burahol, have fruits with low economic value and are rarely planted or are even cut down by the community (Tisnadjaja et al 2006). The use of Annonaceae plants for traditional medicine is widespread.…”
Section: Why Is Conservation Of Annonaceae Important?mentioning
confidence: 99%
“…It was reported that fuit pulp had potential as a natural deodorant since it had adsorbent function and probiotic activation by increase the growth of Bifidobacteria so the population of odorant producing bacteria will be reduced [5]. The fruit pulp of kepel also reported contains high antioxidant [6], and contains alkaloids, flavonoids, polyphenols, triterpenoids, saponins and quinones as well have the effect of anti-implantation [7]. Kepel's leaf contains terpenoids and flavonoids [7].…”
Section: Introductionmentioning
confidence: 99%